Anaemia in lung transplant patient caused by parvovirus B19. Issue 7 (1st July 2000) - Kariyawasam, H H; Gyi, K M; Hodson, M E; Cohen, B J
Abstract : The case history is presented of a lung transplant patient who developed prolonged parvovirus B19 infection with severe transfusion dependent anaemia. The patient was treated with intravenous immunoglobulin after which the haemoglobin rose, together with a reticulocytosis. The patient then remained transfusion free and the virus cleared more than three months after the initial immunoglobulin treatment. The clinical and social implications for this group of patients are discussed.